The role of ultrasonography in the diagnosis of ulcerative colitis - Ülkü DAĞLI,; Ahmet TEZEL,; Sedat BOYACIOĞLU,; Çağlar BAYSAL,; Aysel ÜLKER,; Gülay TEMUÇİN, (Turkish Journal of Gastroenterology, 2019)
-